2021
DOI: 10.1093/ageing/afab066
|View full text |Cite
|
Sign up to set email alerts
|

Developing a virtual geriatric perioperative medicine clinic: a mixed methods healthcare improvement study

Abstract: Background the Geriatric Perioperative Care clinic at North Bristol NHS Trust was suspended in March 2020 during the COVID-19 pandemic. A virtual clinic was piloted to deliver preoperative health optimisation and shared decision-making for patients undergoing critical elective surgery. No literature existed on virtual preoperative clinics for older people to support the development. Objective this healthcare improvement study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Joughin et al recently described implementation of their virtual geriatric perioperative medicine clinic. [31] Comprehensive geriatric assessments were converted to questionnaires which could be utilized during a virtual visit. Patient survey results following implementation demonstrated optimisms over the virtual methodology and particularly in the area of shared decision making.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Joughin et al recently described implementation of their virtual geriatric perioperative medicine clinic. [31] Comprehensive geriatric assessments were converted to questionnaires which could be utilized during a virtual visit. Patient survey results following implementation demonstrated optimisms over the virtual methodology and particularly in the area of shared decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Patient survey results following implementation demonstrated optimisms over the virtual methodology and particularly in the area of shared decision making. [31] Hands et al found that alternative management plans that occurred because of telemedicine proved to be advantageous for both patient and consultants. [32] Similarly, our study highlights that srEFS may be used across a variety of surgical procedures given the diversity of surgical procedures studied.…”
Section: Discussionmentioning
confidence: 99%
“…Patient involvement -In development of the pilot work 67 service user's feedback from a telephone survey has been published (13). -The department of medicine for older people service user group was consulted -Conversations occurred with ten patients from the user group having used the geriatric medicine clinic…”
Section: Amendmentsmentioning
confidence: 99%
“…- In development of the pilot work 67 service user’s feedback from a telephone survey has been published (13).…”
Section: Ethical and Regulatory Considerationsmentioning
confidence: 99%
“…Video clinics can reduce the risk of hospital-acquired infection such as COVID-19, reduce travel with its associated financial and physical burden for patients as well as environmental impact, are delivered at times convenient for patients and doctors, and allow better access to special services for people across the UK. 7 Funding and Support in Kind…”
Section: Study Deliverymentioning
confidence: 99%